Abdominal pain and cirrhosis at diagnosis of hemochromatosis: Analysis of 219 referred probands with HFE p.C282Y homozygosity and a literature review. - James C Barton; J Clayborn Barton; Neha Patel; Gordon D McLaren (PLoS ONE)
Background In hemochromatosis, causes of abdominal pain and its associations with cirrhosis are poorly understood. Methods We retrospectively compared characteristics of referred hemochromatosis probands with HFE p.C282Y homozygosity with/without biopsy-proven cirrhosis: sex, age, diabetes, heavy alcohol consumption, abdominal pain/tenderness, hepatomegaly, splenomegaly, non-alcoholic fatty liver disease, chronic viral hepatitis, ascites, transferrin saturation (TS), serum ferritin (SF), and iron removed by phlebotomy (QFe). We performed logistic regression on cirrhosis using characteristics identified in univariate comparisons. We performed computerized and manual searches to identify hemochromatosis case series and compiled prevalence data on cirrhosis and abdominal pain and causes of abdominal pain. Results Of 219 probands, 57.1% were men. Mean age was 48±13 y. In 22 probands with cirrhosis, proportions of men, mean age, prevalences of heavy alcohol consumption, abdominal pain, abdominal tenderness, hepatomegaly, splenomegaly, and chronic viral hepatitis, and median TS, SF, and QFe were significantly greater than in probands without cirrhosis. Regression analysis revealed three associations with cirrhosis: abdominal pain (p = 0.0292; odds ratio 9.8 (95% CI: 1.2, 76.9)); chronic viral hepatitis (p = 0.0153; 11.5 (95% CI: 1.6, 83.3)); and QFe (p = 0.0009; 1.2 (95% CI: 1.1, 1.3)). Of eight probands with abdominal pain, five had cirrhosis and four had diabetes. One proband each with abdominal pain had heavy alcohol consumption, chronic viral hepatitis B, hepatic sarcoidosis, hepatocellular carcinoma, and chronic cholecystitis, cholelithiasis, and sigmoid diverticulitis. Abdominal pain was alleviated after phlebotomy alone in four probands. In 12 previous reports (1935-2011), there was a negative correlation of cirrhosis prevalence and publication year (p = 0.0033). In 11 previous reports (1935-1996), a positive association of abdominal pain prevalence and publication year was not significant (p = 0.0802). Conclusions Abdominal pain, chronic viral hepatitis, and QFe are significantly associated with cirrhosis in referred hemochromatosis probands with HFE p.C282Y homozygosity. Iron-related and non-iron-related factors contribute to the occurrence of abdominal pain.